TANTANGAN PENYUSUNAN LAPORAN KEUANGAN OLEH PELAKU USAHA MIKRO, KECIL, DAN MENENGAH : STUDI PADA UMKM DI KOTA MOJOKERTO - Kurniawan, Kurniawan (Gapenas Publisher, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, contributing significantly to employment and economic growth. Despite their importance, many MSMEs struggle with financial management, particularly when it comes to producing accurate and timely financial reports. These reports are essential for monitoring the financial health of a business, making informed decisions, attracting investors, and complying with regulatory requirements. One of the main challenges faced by MSME operators is their lack of knowledge and skills in basic accounting principles. Even after receiving training and mentoring, many operators still struggle to prepare financial reports in accordance with accounting standards. This points to a deeper issue within the MSME sector, where a lack of financial literacy hinders business growth and sustainability. In addition to knowledge gaps, MSMEs also face practical obstacles such as limited resources for training and accounting software. The cost of investing in these resources can be prohibitive for many small businesses, especially those operating on tight budgets. Furthermore, the complex and constantly changing regulatory environment in Indonesia adds another layer of difficulty for MSME operators trying to navigate financial reporting requirements. Despite these challenges, there is hope for improvement. By implementing targeted training workshops, simplifying regulations, and providing access to resources such as accounting software and relevant reading materials, MSMEs can enhance their financial management capabilities. Additionally, strengthening support from consultants and offering comprehensive mentoring programs can provide valuable guidance to MSME operators as they work towards producing high-quality financial reports. Ultimately, the success of MSMEs in Indonesia relies on their ability to effectively manage their finances and comply with accounting standards. By addressing the underlying factors that hinder financial reporting, MSME operators can position their businesses for growth and sustainability in the long term. Through collaborative efforts from the government, consultants, and relevant stakeholders, MSMEs can overcome these challenges and thrive in the competitive business landscape of Indonesia.